The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1111/j.1469-7610.1974.tb01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification Behaviors in Third and Sixth Grade Lower and Middle Socio‐economic Status School Children

Abstract: SUMMARY Forty‐eight Ss of Anglo‐Saxon parentage were randomly selected from Were Texas Public Schools. Four groups of 12 Ss each were constituted of third grade lower SES, sixth grade lower SES, third grade middle SES and sixth grade middle SES. Each group was exposed to an array of objects to be grouped. Grouping on a conceptual, non‐conceptual or associational justification was possible. A standardised testing and scoring procedure was followed. Results indicated that the school experience may serve to widen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Analysis of variance is a frequently used technique in the field (e.g. Kofsky 1966; Mallet and Drew 1974). and its use with this type of data has been justified by Popham (1 967).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of variance is a frequently used technique in the field (e.g. Kofsky 1966; Mallet and Drew 1974). and its use with this type of data has been justified by Popham (1 967).…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, studies which have looked at a single response of the subjects cannot answer this question (e.g. Denney 1972;Mallet and Drew 1974). Others have looked at a number of free classification responses made by each subject and have demonstrated that most subjects can reclassify in several different ways (e.g.…”
Section: Introductionmentioning
confidence: 99%